Effect of Phytobiotic Mixture and Organic Acid Supplementation on Growth Performance, Haematobiochemical Profile and Carcass Traits of Broiler Chickens - Yadav, Alka; Gautam, Sachin; Singh, Vijay K. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
This study was undertaken to assess the effect of phytobiotic mixture and organic acid on the performance of broiler chickens. Day-oldbroiler chicks (n=250) were randomly divided into five groups with five replicates of 50 chicks and fed a basal diet with no supplementin the negative control (NC), supplemented with antibiotic (PC), alcoholic extract of 1.0% phytobiotic mixture (HE), 0.1% butyric acid(OA) and 1.0% phytobiotic mixture (alcoholic extract) + 0.1% butyric acid (HEOA). The impact of these supplements on body weightgain (BWG), feed intake (FI), feed conversion ratio (FCR), haemato-biochemical parameters, carcass characteristics, and economics wereassessed in 42 days of experiment. The results revealed that BWG of birds were significantly (p
Keywords: Broilers; Carcass; Haemato-biochemical; Organic acid; Performance; Phytobiotics